(untitled)
Various methods have been employed for the removal of ureteric calculi all over the world. Both Ureteroscopic Pneumatic and Laser lithotripsy are popular procedures for this purpose. However proximal migration of stone fragments are not uncommon in these procedures while treating upper ureteric stones. Extra corporeal shock wave lithotripsy (ESWL) may require to fragment those proximally migrated stones after the ureteroscopic Pneumatic or Laser lithotripsy. To compare the requirement of ESWL in the management of ureteric stone between Holmium Yag Laser and Pneumatic Lithotripsy. This study included 100 patients with upper ureteric stones who underwent ureteroscopic lithotripsy at the Department of Urology, CMH, Dhaka, between October 2010 and September 2012. Laser lithotripsy was used in 50 patients (Group A), and pneumatic lithotripsy was used in the remaining 50 patients (Group B). In each case, the same ureteroscope, video monitor, baskets, or irrigation devices were used. A kidney ureter and bladder radiograph and ultrasonograph were performed on patients one month and three months after lithotripsy. Patients with migrated fragments or insufficient clearance underwent a supplementary procedure such as ESWL. Mean age was 41.9